Pengaruh Edukasi dan Konseling Apoteker terhadap Kepatuhan dan Kualitas Hidup Pasien Kanker Payudara: Literatur Review - Budi, Hermawan Setya; Sutrisno, Entris (Journal of Pharmaceutical and Sciences, 2025)
Pharmacist-led interventions, particularly through education and counselling, play an essential role in supporting treatment adherence and improving the quality of life of breast cancer patients. This article aims to review the influence of pharmacist interventions—such as medication counseling, side effect management, and adherence monitoring—on patient understanding, psychological aspects, and quality-of-life indicators. Results from various experimental studies and randomized controlled trials suggest that structured pharmacist interventions can improve patient understanding, reduce anxiety, and support adherence to long-term therapies such as tamoxifen and chemotherapy. Improvements were also observed in various domains of quality of life, including physical, emotional, and social functioning. However, some studies show inconsistent results, especially in terms of statistical differences in changes in quality of life, which may be due to factors such as sample size, duration of intervention, or other variables, including family support and disease prognosis. Overall, the involvement of pharmacists is an integral part of oncology care, serving as both an educator and a long-term therapy companion.